Chemical Characteristics of Macroscopic Pyrogenic Carbon Following Millennial-Scale Environmental Exposure - Ascough, Philippa L.; Brock, Fiona; Collinson, Margaret E.; Painter, Jon D.; Lane, David W.; Bird, Michael I. (Frontiers in Environmental Science, 2020)
Pyrogenic Carbon (PyC) is ubiquitous in global environments, and is now known to form a significant, and dynamic component of the global carbon cycle, with at least some forms of PyC persisting in their depositional environment for many millennia. Despite this, the factors that determine the turnover of PyC remain poorly understood, as do the physical and chemical changes that this material undergoes when exposed to the environment over tens of thousands of years. Here, we present the results of an investigation to address these knowledge gaps through chemical and physical analysis of a suite of wood PyC samples exposed to the environment for varying time periods, to a maximum of >90,000 years. This includes an assessment of the quantity of resistant carbon, known as Stable Polyaromatic Carbon (SPAC) versus more chemically labile carbon in the samples. We find that, although production temperature is likely to determine the initial ‘degradation potential’ of PyC, an extended exposure to environmental conditions does not necessarily mean that remaining PyC always progresses to a ‘SPAC-dominant’ state. Instead, some ancient PyC can be composed largely of chemical components typically thought of as environmentally labile, and it is likely that the depositional environment drives the trajectory of preservation versus loss of PyC over time. This has important implications for the size of global PyC stocks, which may have been underestimated, and also for the potential loss of previously stored PyC, when its depositional environment alters through environmental or climatic changes.